Pemanfaatan Tool Penunjang Penulisan Artikel Ilmiah Bagi Anggota PERDIBROFI Korwil Jawa Barat - Rizca Haqqu (Jurnal Abdimas Komunikasi dan Bahasa, 2025)
Era transformasi digital menuntut pendidik, khususnya di bidang broadcasting dan film, untuk memiliki kompetensi dalam penulisan dan publikasi ilmiah. Program Pengabdian kepada Masyarakat ini bertujuan meningkatkan literasi akademik guru SMK melalui pelatihan penulisan artikel ilmiah dan pemanfaatan tools digital seperti Mendeley, Grammarly, Turnitin, dan Publish or Perish. Metode yang digunakan adalah participatory action research dengan tahapan FGD, pelatihan hybrid, pendampingan penulisan, serta pengembangan E-Modul BROFI sebagai media pembelajaran mandiri. Hasil pre-test dan post-test menunjukkan peningkatan signifikan dalam pemahaman struktur artikel, sitasi ilmiah, dan kemampuan menulis bebas plagiarisme. Evaluasi kualitatif juga menunjukkan bahwa 86% peserta merasa pelatihan relevan dengan kebutuhan mereka dan berharap program dilanjutkan. E-Modul BROFI yang dikembangkan menyediakan panduan sistematis dan interaktif, serta mendukung keberlanjutan kompetensi guru dalam publikasi ilmiah. Program ini menunjukkan bahwa integrasi pelatihan dan teknologi pendidikan mampu membangun budaya literasi akademik yang berkelanjutan di kalangan guru vokasi. The era of digital transformation demands that educators, particularly in the fields of broadcasting and film, possess competencies in scientific writing and publication. This Community Service Program aims to enhance the academic literacy of vocational high school teachers through training in scientific article writing and the use of digital tools such as Mendeley, Grammarly, Turnitin, and Publish or Perish. The method employed is Participatory Action Research (PAR), involving stages such as Focus Group Discussions (FGDs), hybrid training, writing mentorship, and the development of the BROFI E-Module as a self-directed learning medium. Results from the pre-test and post-test indicate a significant improvement in various aspects of participants' competencies. For example, understanding of article structure improved from 52% to 84%, use of Mendeley from 40% to 85%, paraphrasing and plagiarism detection skills from 38% to 75%, and familiarity with reference search tools (Publish or Perish) from 43% to 78%. Overall, the average increase in technical writing skills exceeded 35%. Qualitative evaluation also showed that 86% of participants found the training relevant to their needs and expressed hope for program sustainability. The developed BROFI E-Module provides a systematic and interactive guide that supports the continuous development of teachers’ competencies in academic publication. This program demonstrates that the integration of participatory training and educational technology can foster a sustainable culture of academic literacy among vocational educators.